PENGARUH TIPE JARAK TANAM TERHADAP ANAKAN, KOMPONEN HASIL, DAN HASIL DUA VARIETAS PADI PADA METODE SRI - Muhammad Hatta (Jurnal Floratek, 2011)
The objective of this study was to test three types of plant spacing on two varieties of rice on growth, yield components, and yield of rice. This experiment used a Randomized Complete Block Design (RCBD) with 3 replications.  Factors studied were types of plant spacing and varieties. The results showed that the types of plant spacing significantly affected rice yield. However, the types of plant spacing did not significantly affect age of flowering, panicle length, and number of grains per panicle. On the rice yield variable, Legowo and triangle (hexagonal) types of plant spacing gave higher yields than rectangular type. Variety significantly affected age of flowering, panicle length, number of grains per panicle, and yield of rice. Pandan Wangi bloomed faster than Cot Irie line. However, Cot Irie line had longer panicles and more grain numbers, and higher yields than Pandan Wangi. There was a significant interaction between varieties and types of plant spacing on a number of productive tillers. On Pandan Wangi, the most productive tillers were found in a rectangular type of spacing, but not significantly different to a triangular type of spacing. The least number of productive tillers was found in a type of Legowo. However, on Cot Irie line, the number of productive tillers did not differ from each other among the types of plant spacing.